Amido rare-earth(iii) and Ca(ii) complexes coordinated by tridentate amidinate ligands: synthesis, structure, and catalytic activity in the ring-opening polymerization of rac-lactide and ε-caprolactone. (4th May 2020) - Rad'kova, Natalia Yu.; Kovylina, Tatyana A.; Shavyrin, Andrei S.; Cherkasov, Anton V.; Fukin, Georgy K.; Lyssenko, Konstantin A.; Trifonov, Alexander A.
Abstract : Y(iii ), Sm(iii ) and Ca(ii ) monoamido complexes coordinated by tridentate amidinate ligand were synthesized and evaluated as initiators of ring-opening polymerization of rac -lactide and ε-caprolactone. Abstract : Complexes [(2-MeOC6 H4 N)C( t Bu)N(2, 6-Me2 C6 H3 )]2 LnN(SiMe3 )2 (Ln = Y (2 ), Sm (3 )) and [(2-MeOC6 H4 N)C( t Bu)N(2, 6-Me2 C6 H3 )]CaN(SiMe3 )2 (THF) (4 ) were obtained by reacting Ln[N(SiMe3 )2 ]3 (Ln = Y, Sm) or Ca[N(SiMe3 )2 ]2 with [2-MeOC6 H4 N]C( t Bu)NH(2, 6-Me2 C6 H3 ) (1 ) in 1 : 2 or 1 : 1 molar ratios, respectively, and were isolated in 76 (2 ), 68 (3 ) and 63% (4 ) yields. In complexes 2 and 3, the amidinate ligands are tridentate due to the intramolecular coordination of the 2-MeO-group to the metal center. Complex 4 exhibits an unusual κ 2 -N, O:η 3 -arene coordination mode of the amidinate ligand. Complexes 2–4 initiate ring-opening polymerization (ROP) of rac -lactide ( rac -LA) and ε-caprolactone (ε-CL) at room temperature and allow for conversion of 1000 equivalents of monomer into polymer within 180–230 min for rac -LA and 1–7 min for ε-CL. Complexes 2 and 3 enable the formation of atactic polymers ( P r = 0.52–0.58) featuring moderate polydispersities (PDI = 1.30–3.06 for polylactide; PDI = 1.48–2.84 for polycaprolactone). When 4 was applied, PDIs were somewhat narrower (1.28–2.43 for PLA; 1.24–2.48 for PCL). Application of the initiating systems 2–4 / i PrOH (1 : 1) leads to the formation of the polymers having close values of the experimental and calculated molecular weights however does not affect strongly the molecular weight distribution. In the presence of 5 equivalents of i PrOH, complexes 2–4 initiate immortal polymerization for both rac -LA and ε-CL. The polymers feature a good match with the experimental and calculated M n but have moderate polydispersities (PDI = 1.28–1.90 for polylactide; PDI = 1.24–1.96 for polycaprolactone).